Implementasi Aplikasi Al-Qur’an Digital pada Siswa Kecanduan Gadget - Olan Olan; Abdullah Idi; Ahmad Zainuri; Ari Sandi (Nazhruna: Jurnal Pendidikan Islam, 2019)
The background of this research is (1) the majority of students have gadgets, (2) students spend more time playing gadgets than reading the Qur'an, (3) students have various social media applications and games but rarely have Al-Qur'an applications' an digital, (4) lack of student awareness in reading the Koran, (5) the need for guidance and motivation by teachers in reading the Qur'an with digital applications. The purpose of this study is to analyze the application of digital Al-Qur'an applications to gadget addicted students and to analyze how to overcome students addicted to gadgets using digital Al-Qur'an applications. Furthermore, this study uses qualitative research using a case study approach. The research subjects were 10 students who were addicted to mobile phones in the learning process at SMP Negeri 3 Tanjung Batu. Data collection uses observation, interviews, and documentation. Data analysis techniques using analysis refers to the concept of Miles and Huberman interactive models, namely: Data Collection, Data Reduction, Data Presentation and Drawing Conclusions. The results showed that the application of digital Al-Qur’an applications in the learning process of reading Al-Qur’an can help direct students to use their cellphones on positive things, and want to change to prefer using their cellphones to read Al-Quran.